THE PROBLEMS OF CONSERVATION OF CORAL REEFS IN NORTHWEST SABAH - Langham, Nigel P.E.; Mathias, Jack A. (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1977)
In March 1974 a survey was made of the coral reefs of NW Sabah centered on three main areas (1) Kota Kinabalu, (2) Kudat and (3) Labuan. At various sites within these areas, the coral reefs were assessed according to the extent of living coral, the damage resulting from fish blasting, mining and sedimentation, and the accessibility for tourism.The coral reefs in this region support a significant fishery accounting for about 30 percent of the fish landings both in weight and monetary value. Reef fish are caught by lines, gill nets, and illegal use of explosives. The latter method has seriously damaged a number of reef habitats resulting in a marked drop in the fauna including valuable fish and invertebrates.Coral mining for limestone used for foundations of buildings and roads has been carried out on accessible reefs near Labuan and Kota Kinabalu. The removal of coral heads has resulted in extensive reef damage especially near Labuan.Recent efforts have been made to preserve these reefs and has led to the establishment of a national park around Pulau.Gaya. However, a number of other areas require protection both to safeguard the fishery and promote tourism.